Cone-Beam Computed Tomography for Evaluation of Apical Transportation in Root Canals Prepared by Two Rotary Systems - Madani, Zahra Sadat; Haddadi, Azam; Haghanifar, Sina; Bijani, Ali (Iranian Endodontic Journal, 2014)
Introduction: Due to the importance of apical transportation during root canal preparation, the aim of the current study was to use cone-beam computed tomography (CBCT) to assess the extent of apical transportation caused by ProTaper and Mtwo files. Methods and Materials: Forty extracted maxillary first molars with 19-22 mm length and 20-40 degrees of curvature were selected. The mesiobuccal canals were prepared using either Mtwo or ProTaper rotary files (n=20). CBCT images were obtained before and after canal preparation to compare the apical transportation in different cross-sections of mesial and distal surfaces. The apical transportation values were analyzed using the SPSS software. The results were compared with student’s t-test and Mann-Whitney U test. Results: There was no significant difference in the extent of apical transportation between Mtwo and ProTaper systems in different canal cross-sections. The apical transportation value was less than 0.1 mm in most of the specimens, which was clinically acceptable. Conclusion: Considering the insignificant difference between the two systems, it can be concluded that both system have low rates of apical transportation and can be assuredly used in clinical settings.